Environment-Based Science Learning to Develop Children's Cognition - Hamdani, Muh; Miyati, Hijul; Rahmat, Mulyana; Astuti, Maria (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Early childhood education is the initial foundation in forming personality, individual character which will influence their life until adulthood. Science process skills in PAUD aim to develop science learning in solving the problems faced. The presence of this article aims to improve cognitive skills through science learning based on the use of the environment for early childhood. Using the literature review or library research method. The results of a review of several scientific literature show that introducing science learning from an early age is very necessary to add insight to students. By learning science, we encourage children to think critically, through simple experiments such as mixing colors or changing an object. so that they can improve their scientific abilities. Apart from that, in science learning we can train children to recognize symptoms that exist in our immediate environment. And also in this case, science and the environment can be combined as a development to develop cognitive abilities in early childhood, as the family environment, school environment and also society are places where children begin to explore their identity.